2001
DOI: 10.1149/1.1362547
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Work Function and Absolute Potential Scale in Solid-State Electrochemistry

Abstract: A two-Kelvin-probe arrangement was used to measure, for the first time in situ, the work functions, ⌽, of the gas-exposed surfaces of porous Pt, Au, and Ag working and reference electrodes exposed to O 2 -He, H 2 -He and O 2 -H 2 mixtures, and deposited on 8% Y 2 O 3 -stabilized ZrO 2 ͑YSZ͒ in a three-electrode solid electrolyte cell. It was found that at temperatures above 600 K the potential difference, U WR , between the working ͑W͒ and reference ͑R͒ electrode reflects the difference in the actual, spillove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 42 publications
2
80
0
6
Order By: Relevance
“…formulated on the basis of (32), should be compared with exact Equation (21). Concluding, the "electron balances" formulated up to 1992 were slavishly related to the stoichiometric reaction notations.…”
Section: Mnomentioning
confidence: 99%
“…formulated on the basis of (32), should be compared with exact Equation (21). Concluding, the "electron balances" formulated up to 1992 were slavishly related to the stoichiometric reaction notations.…”
Section: Mnomentioning
confidence: 99%
“…By thoroughly examining the available literature, we first determine the most reliable experimental benchmark value for the ASHEP. Invoking the fundamental concepts of the absolute potential scale, developed by Trasatti and others, 1,[30][31][32][33][34][35] we then pinpoint the most appropriate choice for the reference level of the computed WF. Subsequently, by briefly revisiting our earlier works, we show how an internal ASHEP reference can be readily established.…”
Section: Introductionmentioning
confidence: 99%
“…102, products It has been shown that gold behaves as a good pseudoreference electrode, since previous NEMCA studies have shown a small variation of its potential (<0.1V) over the range of gaseous compositions used in the present study [15]. In all cases a series of blank experiments was carried out to confirm that the catalytic activity of the Au electrodes was negligible in comparison to that of the Rh catalyst.…”
Section: Productsmentioning
confidence: 63%